2009
DOI: 10.2139/ssrn.1425066
|View full text |Cite
|
Sign up to set email alerts
|

Default, Framing and Spillover Effects: The Case of Lifecycle Funds in 401(K) Plans

Abstract: The authors also acknowledge Vanguard's efforts in the provision of recordkeeping data under restricted access conditions. They benefited from the suggestions of Brigitte Madrian, Alexander Muermann, and Stephen Shore. Opinions, errors, and conclusions are solely those of the authors and do not represent the views of the SSA, any agency of the Federal Government, Vanguard, the MRRC, the NBER or any other institution with which the authors may be affiliated. NBER working papers are circulated for discussion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…13 Few 401(k) plans allow investment in brokerage accounts and only a small fraction of pension assets is invested via these accounts (Keim and Mitchell, 2018;Vanguard, 2019). Further, a large literature shows that retirement plan defaults have large effects on retirement account investment choices (see Madrian and Shea, 2001;Beshears, Choi, Laibson, and Madrian, 2009;Mitchell, Mottola, Utkus, and Yamaguchi, 2009;Cronqvist, Thaler, and Yu, 2018). Online Appendix H shows results when including investments in retirement accounts.…”
Section: Data Sources: American Life Panel Survey and Crspmentioning
confidence: 99%
“…13 Few 401(k) plans allow investment in brokerage accounts and only a small fraction of pension assets is invested via these accounts (Keim and Mitchell, 2018;Vanguard, 2019). Further, a large literature shows that retirement plan defaults have large effects on retirement account investment choices (see Madrian and Shea, 2001;Beshears, Choi, Laibson, and Madrian, 2009;Mitchell, Mottola, Utkus, and Yamaguchi, 2009;Cronqvist, Thaler, and Yu, 2018). Online Appendix H shows results when including investments in retirement accounts.…”
Section: Data Sources: American Life Panel Survey and Crspmentioning
confidence: 99%
“…There is now a large established body of literature that shows that default provisions can have a large impact on savings decisions (for summary, see Beshears, Choi, Laibson and Madrian (2006)). This literature has investigated the role of defaults in decisions regarding participation (e.g., Madrian and Shea 2001), contribution rates (e.g., Choi, Laibson, Madrian and Metrick 2004), asset allocation (e.g., Choi, Laibson and Madrian 2005) and, recently, distributions from DC plans (Mitchell, Mottola, Utkus and Yamaguchi 2009). Typically these studies use changes in 401(k) plan characteristics and default rules at a particular employer as a type of "natural experiment" to investigate the effect of defaults on employee retirement saving, particularly among new hires.…”
Section: Background and Related Literaturementioning
confidence: 99%
“…Hence, the lifecycle pension strategy is often considered to be the default pension investment strategy in pension practice. Other studies have shown that the lifecycle pension strategy is a flexible portfolio management strategy that could be combined with other pension concepts in order to achieve different pension targets (Mitchell et al 2009) However, recent studies have cast new doubt on the classical lifecycle pension investment strategy. For instance, although lifecycle pension strategies have been shown to be superior to money market funds, they often underperform the balanced mandates that hold a constant asset allocation of 50% risky assets and 50% risk-free assets throughout the pension accumulation phase (Blanchett and Kaplan 2018).…”
Section: Literature Reviewmentioning
confidence: 99%